Endless hunger. Issue 1 - McMahon, John, (Zine creator) (Nashville, Tennessee : John McMahon)
Contains strong language and adult themes.
Cover title.
Keywords: McMahon, John, -- (Zine creator); Men -- United States -- Conduct of life; Social interaction -- United States; United States -- Social life and customs; Zines